Visual Effects Filmbilder aus dem Computer - Flueckiger, Barbara (Zürcher Filmstudien, 2023)
Opinions differ on the computer-generated image. Is the computer a cold, calculating machine that takes the place of humans and robs film of its once analog soul? The author presents the technical basics and visual aspects of the computer-generated film image and explains the aesthetic consequences. The author examines the technical foundations of 3D modeling and animation, their development and practice and discusses their difference to conventional methods of cinematic imaging. But the aesthetic aspects are also analyzed: aesthetic consequences of the collision of grain and pixels, of additive and subtractive color systems, of conventional photography and mathematical-scientific modeling algorithms A standard work!